New Developments in Marine Biotechnology - Le Gal, Yves; Halvorson, Harlyn O. (Plenum Press, 1998)
Past efforts to colonize the environment and domesticate living species, coupled with scientific research, have resulted in the possession (but not always the real control) by humans of any available terrestrial space. However, oceans, which represent up to two thirds of the surface of the planet, had not been really approached until the middle of this century. As oceanographic science develops, the picture of a rich, diverse, complex and also, in many respects, specific marine life, is coming into view. In a broad sense, marine biotechnologies can be understood as the various means or techniques of managing marine living systems for the benefit of mankind. The first goal we have is for marine life to provide biomass for food. However, today it is not certain that a significant increase of total world fisheries' catches will be possible in the future. There are several ways to address this. First, we need to generate better, more complete, or different uses of the biomass actually fished. This is mainly a matter of upgrading fish and fish wastes. Second, we need to artificially grow the living species. This falls within the scope of cell cultivation and of aquaculture. Both approaches have to be appreciated si multaneously in terms of biology, ecology, and economy. In both approaches, profit improvements are linked to the introduction of biotechnological methods and to the use of biotechnological processes